Narrative and the Politics of Meaning in a "Post-Fact" World. (22nd November 2017) - Loseke, Donileen R
Abstract: How is it possible to motivate publics to do something about social problems when there is no agreement about what is and what is not moral, about who does and who does not deserve help, about what is justice and what is tyranny? I explore the importance of narratives in public moral arguments and argue that narrative productions of moral and emotional meanings are a central characteristic of the social processes of power and politics within our globalized, heterogeneous, morally fragmented, rapidly changing, and mass-mediated world.